Cerebral salt wasting following traumatic brain injury. (4th April 2017) - Taylor, Peter; Dehbozorgi, Sasan; Tabasum, Arshiya; Scholz, Anna; Bhatt, Harsh; Stewart, Philippa; Kumar, Pranav; Draman, Mohd S; Watt, Alastair; Rees, Aled; Hayhurst, Caroline; Davies, Stephen
Summary: Hyponatraemia is the most commonly encountered electrolyte disturbance in neurological high dependency and intensive care units. Cerebral salt wasting (CSW) is the most elusive and challenging of the causes of hyponatraemia, and it is vital to distinguish it from the more familiar syndrome of inappropriate antidiuretic hormone (SIADH). Managing CSW requires correction of the intravascular volume depletion and hyponatraemia, as well as mitigation of on-going substantial sodium losses. Herein we describe a challenging case of CSW requiring large doses of hypertonic saline and the subsequent substantial benefit with the addition of fludrocortisone. Learning points: The diagnosis of CSW requires a high index of suspicion. Distinguishing it from SIADH is essential to enable prompt treatment in order to prevent severe hyponatraemia. The hallmarks of substantial CSW are hyponatraemia, reduced volume status and inappropriately high renal sodium loss. Substantial volumes of hypertonic saline may be required for a prolonged period of time to correct volume and sodium deficits. Fludrocortisone has a role in the management of CSW. It likely reduces the doses of hypertonic saline required and can maintain serum sodium levels of hypertonic saline.